1996
DOI: 10.1111/1523-1747.ep12340161
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-12 Inhibits Angiogenesis Induced by Human Tumor Cell Lines In Vivo

Abstract: Tumor cell-induced angiogenesis, i.e., new blood vessel formation within tumor tissue, is an essential requirement for the growth of solid neoplasms. Interleukin-12 (IL-12) inhibits growth of a variety of experimental tumors in vivo. We tested whether antitumor activity of IL-12 is related to the inhibition of angiogenesis induced by tumor cell lines. Angiogenesis was induced in x-ray immunosuppressed Balb/c mice by intradermal injection of the following human tumor cells: T47D, originating from mammary carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 30 publications
2
35
1
Order By: Relevance
“…The mechanisms of IL-12-mediated antitumor activity depend not only on activation of innate and adaptive effector immune mechanisms, but also on inhibition of angiogenesis (16)(17)(18). The latter is mediated by induction of IFN-␥, which in turn leads to release of the antiangiogenic chemokines CXCL9, CXCL10, and CXCL11.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanisms of IL-12-mediated antitumor activity depend not only on activation of innate and adaptive effector immune mechanisms, but also on inhibition of angiogenesis (16)(17)(18). The latter is mediated by induction of IFN-␥, which in turn leads to release of the antiangiogenic chemokines CXCL9, CXCL10, and CXCL11.…”
Section: Discussionmentioning
confidence: 99%
“…IL-12, which is produced predominantly by antigen-presenting cells, drives T helper (Th1) responses, enhances T and natural killer (NK) cell cytotoxicity, and induces IFN-␥ production by T and NK cells (4,[7][8][9]. In addition, we have shown that IL-12 contributes to the regulation of normal human B cell function through stimulation of IgM synthesis and IFN-␥ production (10).IL-12 exerts antitumor activity through IFN-␥-dependent and independent mechanisms (11-15), which include modulation of the immune system and antiangiogenesis (16)(17)(18). We have recently demonstrated that the IL12RB2 gene acts as a tumor suppressor in human chronic B cell malignancies (14) and, accordingly, that aging IL12rb2 knockout (KO) mice develop spontaneously B cell tumors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo studies demonstrated that the antitumor effect of recombinant IFN-b may be mediated, at least in part, via angiogenesis inhibition rather than antiproliferative activity (Hong et al, 2000) and that IFNa and retinoic acid have remarkably synergistic antiangiogenic effects able to inhibit both the growth and the neovascularization of head and neck squamous cell carcinoma injected into the floor of the mouth of nude mice (Lingen et al, 1998). Other in vivo studies evidenced that mice treated with rat antibody raised against murine IFN-g results in neutralizing the antiangiogenic effect of murine interleukin-12 (IL-12) (Majewski et al, 1996). This phenomenon indicates that IFN-g is a mediator of the antiangiogenic effect of IL-12 and that the mechanism of antitumor action of IL-12 may depend not only on the immunostimulatory activity of this cytokine but also on its effect on tumor cell-induced angiogenesis.…”
Section: Antiangiogenic Factorsmentioning
confidence: 96%
“…The mechanism by which IL-12 exerts this antitumor effect is not known, but is likely to involve a combination of activities including the modulation of T cell populations, stimulation of IFN-␥ production, and inhibition of angiogenesis. [37][38][39][40][41] A phase I gene therapy clinical trial employing a bicistronic retroviral vector expressing both human IL-12 subunits has been initiated in patients with metastatic cancer. 42 Adeno-associated viruses (AAV) are single-stranded DNA parvoviruses that offer several advantages over other gene transfer vectors.…”
mentioning
confidence: 99%